An approach to textile dye removal using sawdust from Aspidosperma polyneuron - Galvão Morão, Luana [UNESP]; Dilarri, Guilherme [UNESP]; Renato Corso, Carlos [UNESP] (Taylor & Francis, 2017)
The textile industry is responsible for discarding wastewater contaminated with dyes. The timber industry generates waste in the form of sawdust. The aim of the present study was to evaluate the adsorptive potential of sawdust obtained from the Aspidosperma polyneuron tree for the removal of the textile dye from wastewater. Sawdust was subjected to different pre-treatments (acid, alkaline and polyethyleneimine) in order to increase its adsorption capacity. Based on the results from the isotherms, treatment with polyethyleneimine (PEI) led to the greatest adsorption capacity and fits the Freundlich model, indicating cooperative adsorption. Other treatments with sawdust best fit the Langmuir model, but the untreated sawdust presented better results than the treated sawdust. These results were only surpassed by sawdust treated with PEI. A. polyneuron revealed good potential for use as an adsorbent to remove dyes, which is a novel result, since to date there is no study on its use as a sorbent material.
Keywords: Adsorption; isotherm; polyethyleneimine; sawdust; wastewater